The Influence of Artificial Intelligence and Machine Learning on the Platform Business Landscape - Jitvirat, Kosol; Charoenvaichat, Kandhicha; Chongsirithitisak, Thanathon (Journal of Humanities and Social Sciences Thonburi University, 2024)
This research aims to study the influence of artificial intelligence and machine learning on the platform business landscape. It is qualitative research, using content analysis methods and participatory and non-participant observation, the scope of the study is a business platform that uses artificial intelligence, and machine learning on both domestic and international platforms, select a sample to be a specific case study, according to the phenomenon of the research question that needs to be answered, a total of 150 case studies were systematically reviewed, to ensure that the platform related to what is being studied. Use a data recording form, keyword research tools, and content management systems are research tools, then take the obtained data and analyze it together, using an inductive analysis method combined with analysis by comparing events, check the reliability of the information using triangular inspection. The findings appear to be in the same direction. Research showed that artificial intelligence and machine learning influence the platform business landscape: 1) Data-driven Decision-making, 2) Personalization, 3) Efficient Matching, 4) Automation and Optimization, 5) Fraud Detection and Security, 6) Predictive Analytics, 7) Enhanced User Experience, 8) New Business Models, 9) Marketplace Dynamics, and 10) Regulatory Challenges.